Preparation method and application of three-dimensional flower-shaped NixPy-NixSy composite structure
By combining hydrothermal reaction and chemical vapor precipitation, using phosphorus powder instead of NaH2PO2, a three-dimensional flower-like NixPy-NixSy composite structure was successfully prepared, solving the problems of few active contacts, irregular surfaces and toxic gas emissions in the prior art, and achieving efficient phosphating and excellent humidity sensing performance.
Patent Information
- Application Number
- CN202411258038.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing NixPy-NixSy composite synthesis method results in few active contacts, irregular surfaces, requiring a high-temperature environment and producing toxic gas PH3, resulting in low phosphating efficiency and poor humidity sensor performance.
Using a combination of hydrothermal reaction and chemical vapor precipitation method, the solution of nickel nitrate hexahydrate, ammonium fluoride and urea was stirred and heated, and phosphorus powder was used instead of NaH2PO2, and the reaction temperature was controlled at 120-200°C to form a three-dimensional flower-like NixPy-NixSy composite structure.
The composite material with regular morphology and excellent dispersion is formed, which increases active contacts, improves phosphating efficiency, reduces the emission of toxic gases, and improves the response recovery time and sensing performance of the humidity sensor.
Smart Images

Figure CN119566317A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to Ni x P y -Ni x S y Composite material preparation field, especially three-dimensional flower-shaped Ni x P y -Ni x S y The invention relates to a preparation method of a composite structure and its application. Background Art
[0002] In recent years, transition metal oxides, hydroxides, phosphides and sulfides have attracted wide attention in the research community due to their excellent physical and chemical properties. Among them, transition metal phosphides (TMPs), as an n-type semiconductor material, have semi-metallic properties compared with p-type semiconductor transition metal oxides or hydroxides, so they are more conducive to electron transfer between interfaces. x P y ) Because of its unique d-orbital incompletely filled electronic structure, it exhibits superior properties compared to other transition metal phosphides. Studies have shown that nickel phosphide has more unsaturated atoms on its surface, making it easier to transmit electrons, and the stronger Ni-P bonds improve its resistance to chemical corrosion and oxidation, while also increasing its thermal stability and hardness, and it is not even affected by strong acid or strong alkaline environments. Because of its good conductivity, excellent chemical stability and environmental friendliness, nickel phosphide is considered to be one of the most competitive candidate materials in the fields of batteries, electrocatalysis, and water electrolysis.
[0003] In addition, Ni in transition metal sulfides (TMSs) x S y Due to its superior redox properties, abundant edge active sites and low cost, it has become another very popular candidate material. Studies have found that the heterostructure constructed by TMPs and TMSs can make two anions with different electronegativity (S>P) mutually regulate each other, optimize the electronic structure of the interface, and facilitate the electron transfer on the surface of the composite material. At the same time, Ni x P y After Ni x S y After modification, the charges on the heterojunction interface are redistributed, making Ni x P y -Ni x S y Composite materials have better physical and chemical properties.
[0004] Combining the advantages of transition metal sulfides under alkaline conditions and rationally compounding them with transition metal phosphides is a promising strategy for achieving high-performance composite materials. x P y -Ni x S y The synthesis of composite materials has gradually emerged in a large number of article reports.
[0005] In the prior art, Ni x P y -Ni x S y The synthesis methods of composite materials mainly include electrodeposition, programmed temperature reduction, NaH 2 PO 2 ˙H 2 O is the phosphorus source of chemical vapor precipitation and step-by-step hydrothermal method. Among them, electrodeposition is the process of electrochemically depositing metals from aqueous solutions, non-aqueous solutions or molten salts of their compounds. This process needs to be carried out under electrolyte conditions and is easily affected by factors such as electrolyte composition, pH value, temperature, and current density. Therefore, the transition metal phosphosulfides synthesized by electrodeposition are mostly solid particles that are agglomerated together and have different sizes, which greatly reduces the number of active sites and is not conducive to improving the performance of composite materials. The common method of obtaining phosphides by temperature-programmed reduction is to use hydrogen to temperature-programmed reduction of the corresponding phosphates. This synthesis method is characterized by a high reaction temperature, which may cause the active phase particles of the phosphide to become larger during the formation process. The size of the particles cannot be precisely controlled, so it is difficult to estimate the turnover frequency, and it is also impossible to directly evaluate the relative reactivity of the crystal face. NaH 2 PO 2 ˙H 2 Chemical vapor precipitation with O as the phosphorus source is the most commonly used method for phosphosulfurization of substances. 2 PO 2 ˙H 2 O acts as a phosphorus source to phosphate the target substance, but NaH 2 PO 2 ˙H 2 When O is heated to above 200°C, it will rapidly decompose and release highly toxic and self-igniting PH 3 Gas, there is a certain degree of danger, the phosphorus source commonly used in the step-by-step hydrothermal method is NaH 2 PO 2 ˙H 2 O, sulfur source is Na 2 Compared with chemical vapor precipitation, the phosphosulfurization efficiency is very low and side reactions are prone to occur in the reaction system. Summary of the invention
[0006] The object of the present invention is to provide a three-dimensional flower-shaped Nix P y -Ni x S y Preparation method and application of composite structure to solve the problem of Ni x P y -Ni x S y Composite materials have few active contacts, irregular surfaces, and require high temperature environments to guide them, which results in a large amount of toxic and harmful gases during the synthesis process. 3 The emissions, low phosphating efficiency, and poor response recovery time and sensing performance of humidity sensors made of transition metals make them inapplicable to practical applications.
[0007] The present invention provides a three-dimensional flower-shaped Ni x P y -Ni x S y The preparation method and application of the composite structure are completed according to the following steps:
[0008] 1. Prepare a reaction solution, dissolve nickel nitrate hexahydrate, ammonium fluoride and urea in a solvent, place on a stirring table and stir magnetically until dissolved to obtain a uniformly mixed solution.
[0009] The molar ratio of the nickel nitrate hexahydrate to the urea is set to 1:(0.5-2); the molar ratio of the nickel nitrate hexahydrate to the ammonium fluoride is 1:(0.5-2); the volume ratio of the total molar number of the nickel nitrate hexahydrate and the urea to the solvent is 1:(7-20), and the solvent consists of ethanol and deionized water; the total volume of the ethanol and the deionized water is 30 mL, and the concentration of the ethanol is (10-50) wt%.
[0010] 2. Sample preparation: The stirred and evenly mixed solution is placed in a stainless steel reactor and sealed for high temperature reaction, then cooled to room temperature, and then the mixed solution is fully washed with a cleaning solution to remove impurities, and then centrifuged and dried.
[0011] The high temperature is between 120-200° C., the reaction time is between 1-24 hours, the inner lining of the stainless steel reactor needs to be made of polytetrafluoroethylene, and the cleaning solution is a mixed solution of deionized water and ethanol.
[0012] 3. Making pure Ni x P y : The dried sample and phosphorus powder are placed in a tube furnace and heated for several hours under inert gas conditions to obtain pure Ni x P y .
[0013] The mass of the sulfur powder is 10-30 times the mass of the dried sample, and the sulfur powder is calcined at a heating rate of 1-10°C / min to obtain a flower-like Ni with a smooth surface. x P y .
[0014] 4. Composite material Ni x P y -Ni x S y Generate: Ni x P y The composite material Ni x P y -Ni x S y .
[0015] Among them, the Ni x P y and the sulfur powder are respectively loaded into two alumina porcelain boats, wherein the mass of the sulfur powder is Ni x P y 10-30 times of that of NiO2, and heated to above 450°C at a heating rate of 1-10°C / min in an inert gas environment to obtain flower-like NiO2 with small particles attached to the surface. x P y -Ni x S y Composite materials.
[0016] 5. The three-dimensional flower-shaped Ni x P y -Ni x S y The composite structural material powder is ground into a paste with a small amount of anhydrous ethanol, and the mixture is drop-coated on the Au interdigital electrode and dried at 70°C. It can be used in the humidity-sensitive field to construct a new type of humidity sensor.
[0017] Compared with the prior art, the beneficial effects of the present invention are:
[0018] In the present invention, the method combines the advantages of hydrothermal reaction and chemical vapor deposition, and can not only form a composite material with a regular morphology, but also has excellent dispersion between particles of the composite material, has a relatively large specific surface area, forms more active contact positions, and promotes the penetration and diffusion of water molecules while providing more adsorption sites for water molecules. The reaction temperature is much lower than the high temperature required by the programmed temperature reduction method, thereby avoiding the problem of the phosphide active phase particles becoming larger during the formation process, making it easier to control the particle size, and thus facilitating the estimation of turnover frequency and the evaluation of the relative reactivity of the crystal surface. In the field of material synthesis, the traditional phosphating process will produce toxic and harmful PH 3 Gas, which not only pollutes the environment, but also threatens the health of operators. Innovative use of phosphorus powder instead of NaH 2 PO 2 ˙H 2 O thus reducing toxic and harmful gases PH 3 This means that the production process can not only reduce the emission of harmful substances, but also reduce the pressure on the ecosystem, achieve environmental protection, and reduce the potential harm to the environment and human health. By optimizing the conditions and process of the phosphating reaction, phosphorus powder is used instead of NaH 2 PO 2 This method significantly improves the phosphating efficiency, which means that a higher conversion rate can be achieved in a shorter time and more target products can be produced, thereby reducing production costs and improving production efficiency. More importantly, the material has excellent humidity sensitivity and is the first to apply transition metal phosphosulfides to the humidity-sensitive field under high temperature conditions to construct a new type of humidity sensor. The synthesized composite material can well reduce the response recovery time of the humidity sensor and improve the sensing performance, thus opening up a new path for the humidity sensing field of transition metal phosphosulfides under high temperature conditions. In addition, the synthesis method of the material is simple, efficient and environmentally friendly, and the solvents used are water and ethanol, which are environmentally friendly and more suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The present invention prepares three-dimensional flower-shaped Ni x P y -Ni x S yFlow chart of the preparation of the composite structure;
[0021] Figure 2 Ni(OH) in Example 2 of the present invention 2 -Ni x P y XRD spectrum of
[0022] Figure 3 SEM image of Example 3 of the present invention (a) Fe x P y -Fe x S y ,(b)Co x P y -Co x S y ,(c)Cu x P y -Cu x S y ,(d)Zn x P y -Zn x S y ;
[0023] Figure 4 The pure phase Ni in Example 1 of the present invention x P y SEM images of
[0024] Figure 5 The pure phase Ni in Example 1 of the present invention x P y XRD spectrum of
[0025] Figure 6 Ni in Example 1 of the present invention x P y -Ni x S y SEN images of composite materials;
[0026] Figure 7 Ni prepared in Example 1 of the present invention x P y -Ni x S y XRD spectra of the composite materials;
[0027] Figure 8 Ni prepared in Example 3 of the present invention x P y -Ni x S y Response recovery curve of the composite material in one cycle in the range of 11-97% RH;
[0028] Fig. 9 Example 3Ni of the present invention x P y -Ni x S y Response recovery curves of the composite materials in the range of 11-97% RH;
[0029] Fig.10 Example 4Ni of the present invention x P y -Ni x S y Dynamic response recovery characteristics of composite materials;
[0030] Fig.11 Ni prepared in Example 4 of the present invention x P y -Ni x S y Humidity hysteresis curves of composite materials;
[0031] Fig.12 Ni prepared in Example 4 of the present invention x P y -Ni x S y Reproducibility of composite materials in the 11-97% RH range;
[0032] Fig.13 Ni prepared in Comparative Example 1 of the present invention x P y -Ni x S y Complex impedance curves of composite materials in different humidity ranges. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0034] The components of the embodiments of the present invention generally described and shown in the drawings herein may be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention.
[0035] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0036] Combine the following Figures 1 to 13 As shown, the embodiment of the present invention provides a three-dimensional flower-shaped Ni x P y-Ni x S y The preparation method and application of the composite structure, various raw materials used in the format examples of the present invention, unless otherwise specified, are commercially available.
[0037] Embodiment 1:
[0038] Raw materials: nickel nitrate hexahydrate, urea, ammonium fluoride, ethanol and deionized water.
[0039] This embodiment provides a method for three-dimensional flower-shaped Ni x P y -Ni x S y The preparation method of the composite structure is completed according to the following steps:
[0040] 1. Dissolve nickel nitrate hexahydrate, urea and ammonium fluoride in a solvent consisting of ethanol and deionized water in a molar ratio of 1:2:1, wherein the ethanol concentration is (10-50) wt%, and stir magnetically until dissolved to obtain a uniformly mixed solution.
[0041] 2. The stirred solution in step 1 was transferred to a stainless steel reactor lined with polytetrafluoroethylene, sealed, and reacted at high temperature. After cooling naturally to room temperature, the reacted solution was fully washed with deionized water and ethanol, and dried in an oven at 70°C for 12 hours to obtain a three-dimensional micron flower-shaped Ni(OH) 2 Precursor.
[0042] 3. Ni(OH) obtained in step 2 2 The precursor and phosphorus powder are loaded into two alumina ceramic boats respectively, where the mass of phosphorus powder is Ni(OH) 2 The precursor is 10-30 times thick, and is heated to above 450°C in an inert atmosphere at a heating rate of 1-10°C / min to obtain a flower-like Ni with a smooth surface. x P y .
[0043] 4. Ni obtained in step 3 x P y and sulfur powder are loaded into two alumina porcelain boats respectively, where the mass of sulfur powder is Ni x P y The Ni-based material is 10-30 times thicker than the original material and heated to above 450°C at a heating rate of 1-10°C / min in an inert atmosphere to obtain a flower-like Ni-based material with small particles attached to the surface. x P y -Ni x S y Composite materials.
[0044] Among them, the Ni in step 3 is obtained by scanning electron microscopy technology. x P y The sample surface image shows the microscopic morphology and structural characteristics of the sample surface. The SEM image is shown in Figure 4 , its XRD test Figure 5 It can be seen that after calcination, the crystallization is complete, and the XRD diffraction peak is consistent with Ni x P y There is a good correspondence.
[0045] At the same time, the Ni in step 3 was obtained by scanning electron microscopy technology. x P y -Ni x S y Composite material sample surface image, showing the microscopic morphology and structural characteristics of the sample surface Ni x P y -Ni x S y The SEM image of the composite material is shown in Figure 6 , its XRD test Figure 7 It can be seen that after calcination, the crystallization is complete, and the XRD diffraction peak is consistent with Ni x P y -Ni x S y There are good correspondences.
[0046] Embodiment 2:
[0047] In this embodiment, phosphorus powder is used instead of NaH 2 PO 2 , which can improve the phosphating efficiency.
[0048] Theoretically, 1 mol of phosphorus powder can generate 1 mol of Ni x P y , but for NaH 2 PO 2 ˙H 2 For example, 1 mol of NiO is generated. x P y , then about 2.7 mol NaH 2 PO 2 ˙H 2 O. (As shown in the following reaction formula)
[0049] 8H 2 PO 2 - →4PH 3 +4HPO 4 2- ①
[0050] 3 x Ni 2 + +12OH - +4PH 3 →3Ni x P y +6H 2 O+P↑ ②
[0051] xP 2 +→Ni x P y ③
[0052] The above conclusions are also confirmed by experiments:
[0053] Now weigh 1 mol of NaH 2 PO 2 Ni(OH) 2 Phosphate treatment was performed and XRD was used to characterize the product. Figure 2 It can be seen that the product is Ni(OH) 2 and Ni x P y It is composed of two phases. 2 Not completely converted to Ni x P y .
[0054] Embodiment 3:
[0055] The present invention discloses a method for synthesizing Ni with a three-dimensional flower-like structure x P y -Ni x S y The preparation method of composite materials is not limited to specific metals, but can also be widely used in the phosphosulfurization process of various transition metals, showing excellent universality. This special composite material structure gives the material unique physical and chemical properties, enabling them to play an important role in different application fields, such as Figure 3 As shown, the microstructures of these composites show rich diversity and complexity. When discussing the core value of this invention, several key points need to be emphasized. First, the universality of this method means that it can be extended to a variety of transition metals, which provides a wide range of material choices for research and industrial applications. Second, the three-dimensional flower-like Ni prepared by this method x P y -Ni x S y Composite materials have shown excellent performance in many fields such as catalysis, energy storage, and sensors due to their unique structural characteristics. Figure 3The microstructure images of the composite materials shown in the present invention not only confirm the complexity and diversity of the materials, but also reflect the accuracy and controllability of the preparation method. These images provide an intuitive basis for studying the relationship between the structure and performance of the materials, and further provide important information for optimizing the performance and application of the materials. In summary, the preparation method provided by the present invention not only provides a novel method for preparing three-dimensional flower-shaped Ni x P y -Ni x S y The production of composite materials provides an efficient and universal way, and promotes the innovative development of materials science, providing new solutions for material needs in different fields. Figure 3 The composite material structures shown can further explore and expand the potential applications of these materials and contribute to scientific and technological progress.
[0056] Embodiment 4:
[0057] Three-dimensional flower-shaped Ni x P y -Ni x S y Specific implementation of the moisture-sensitive performance test of composite structures:
[0058] Step 1: Preparation of humidity sensor
[0059] The three-dimensional flower-shaped Ni x P y -Ni x S y The composite structural material powder is ground into a paste with a small amount of anhydrous ethanol, and the mixture is drop-coated on the Au interdigital electrode and dried at 70°C. It can be used in the humidity-sensitive field to construct a new type of humidity sensor.
[0060] Step 2: Moisture Sensitivity Test
[0061] Reagents LiCl <![CDATA[CH 3 COOK]]> <![CDATA[MgCl 2 ]]> <![CDATA[K 2 CO 3 ]]> <![CDATA[Mg(NO 3 ) 2 ]]> Relative humidity (%RH) 11 22 32 43 54 Reagents KI NaCl KCl <![CDATA[Pb(NO 3 ) 2 ]]> Relative humidity (%RH) 69 75 84 97
[0062] Table 1 Different relative humidity configuration table
[0063] The device was placed in 9 solutions containing different saturated salts (LiCl, CH 3 COOK、MgCl 2 , K 2 CO 3 Mg(NO 3 ) 2 , KI, NaCl, KCl, Pb(NO 3 ) 2) in a glass jar to test the humidity sensing performance. The relative humidity values (RH) of the above 9 saturated salt solutions at room temperature (25°C) are 11%, 22%, 32%, 43%, 54%, 69%, 75%, 84%, and 97%, respectively. The humidity sensitivity performance of the humidity sensor is tested by an LCR digital bridge meter analyzer (TH2829A, Changzhou, China) under the conditions of an AC voltage of 1V and an operating frequency range of 200Hz-200kHz. The test results are shown in six charts, namely Figures 8 to 13 , these charts record in detail the response of the material under different relative humidity conditions, thus comprehensively demonstrating the performance of the material as a humidity sensor. From these data, it can be seen that the material of the present invention can accurately sense changes in different humidity levels and exhibit good stability and reliability. In summary, the humidity sensing performance tests conducted in a series of saturated salt solutions fully verify the excellent performance of the material of the present invention in humidity detection. These test results not only prove the high sensitivity of the material to humidity changes, but also show its potential huge application value in the field of environmental monitoring and control.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Three-dimensional flower-shaped Ni x P y -Ni x S y The method for preparing a composite structure is characterized by: The following steps are involved: Sp1: Prepare a reaction solution: dissolve nickel nitrate hexahydrate, ammonium fluoride and urea in an ethanol solvent, place on a stirring table and stir magnetically until dissolved to obtain a uniformly mixed solution; Sp2: Sample preparation: The uniformly mixed solution obtained in Sp1 is placed in a stainless steel reactor and sealed for high temperature reaction, then cooled to room temperature, and then the mixed solution is fully washed with a cleaning solution to remove impurities, and then centrifuged and dried to obtain a sample; Sp3: Making pure Ni x P y : The dried sample and phosphorus powder are placed in a tube furnace and heated for several hours under inert gas conditions to obtain pure Ni x P y ; Sp4: Composite material Ni x P y -Ni x S y Generate: Ni x P y The composite material Ni is obtained by placing the composite material Ni and sulfur powder in a tube furnace and heating it for several hours under inert gas conditions. x P y -Ni x S y .
2. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: In the step Sp1, the molar ratio of the nickel nitrate hexahydrate to the urea is 1:(0.5-2), the molar ratio of the nickel nitrate hexahydrate to the ammonium fluoride is 1:(0.5-2), and the volume ratio of the total moles of the nickel nitrate hexahydrate and the urea to the ethanol solvent is 1:(7-20).
3. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: In the step Sp1, the ethanol solvent consists of ethanol and deionized water, wherein the total volume of the ethanol and the deionized water is 30 mL, and the concentration of the ethanol is (10-50) wt%.
4. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: In the sample preparation step of Sp2, the dried sample and the phosphorus powder are heated in the tubular furnace and the inert gas at a temperature between 120 and 200° C., and the reaction time is between 1 and 24 hours.
5. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: In the sample preparation step of Sp2, the cleaning solution is a mixed solution of deionized water and ethanol.
6. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: The Sp3 pure phase Ni x P y In the step, the heating temperature is not less than 350°C.
7. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: The Sp4 Ni composite material x P y -Ni x S y In the generating step, the heating temperature is not less than 350°C.
8. The three-dimensional flower-shaped Ni according to claim 1 x P y -Ni x S y The method for preparing a composite structure is characterized by: The inner lining of the stainless steel reactor is made of polytetrafluoroethylene.
9. Three-dimensional flower-shaped Ni x P y -Ni x S y The application of composite structure, the three-dimensional flower-shaped Ni x P y -Ni x S y The composite structure is used in the moisture-sensitive field and is characterized by: The three-dimensional flower-shaped Ni x P y -Ni x S y The composite structural material powder is mixed and ground with a small amount of anhydrous ethanol to form a paste-like substance; The paste was then drop-coated on the Au interdigital electrode and dried at 70°C; After processing, it can be applied to the humidity-sensitive field to build a new type of humidity sensor.
Citation Information
Patent Citations
Preparation method of nano petaline Ni(OH)2
CN102774893A
New method for two-step process preparation of nickel sulfide
CN104261490A
Preparation method of flower-like nickel sulfide material and application of flower-like nickel sulfide material in super capacitor
CN105489390A
Nickel sulfide electrode material and preparation method and application thereof
CN110078137A
Preparation method and application of nickel sulfide / nickel hydroxide flower-like nano composition
CN110526305A
